A case of lung volume reduction surgery with decortication for a septic patient in respiratory failure. (2015) - Tarazi, M.; Mayooran, N.; Anwer, M.; Anjum, M.N.; Doddakula, K.
Highlights: Decortication and lung volume reduction surgery are both major operations and each has its independent risk of morbidity and mortality. Bullae can produce signs and radiologic appearances of pneumothorax and it is important to differentiate them before treatment. The differentiation between giant bulla and pneumothorax can be very difficult and often leads to inaccurate diagnosis and management. The NETT trial showed that patients most likely to benefit from lung volume reduction surgery have heterogeneously distributed emphysema involving the upper lung zones predominantly. Our case demonstrates the feasibility of achieving an excellent overall outcome with a combination of complex procedures. Abstract: Introduction: Decortication and lung volume reduction surgery are both major operations and each has its independent risk of morbidity and mortality. Case report: We present the case of a 41 year old gentleman with left sided empyema and giant bullae of the upper lobe with an active air leak that was transferred to our tertiary referral centre for further management. We performed emergency left thoracotomy, decorticated the left lower lobe with extensive lung volume reduction surgery of the upper lobe. Patient's respiratory status significantly improved along with excellent radiological results. Conclusion: Our case demonstrates that a combination of complex procedures is feasible with excellent outcomes.